2022
DOI: 10.1039/d2ta06686f
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide wrapped hollow mesoporous carbon spheres as a dynamically bipolar host for lithium–sulfur batteries

Abstract: Lithium−sulfur batteries (LSBs) hold a great potential as the next-generation electrochemical energy storage and conversion system owing to their high theoretical specific capacity (1675 mAh g-1). However, the shuttling of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
(73 reference statements)
0
4
0
1
Order By: Relevance
“…31 The ether/hydroxyl and carboxyl surface groups are thought to be beneficial in the hindering of the polysulfide-shuttle by immobilisation of the polysulfides; oxygen surface concentrations for all carbon samples are shown in Table 4. 32,33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The ether/hydroxyl and carboxyl surface groups are thought to be beneficial in the hindering of the polysulfide-shuttle by immobilisation of the polysulfides; oxygen surface concentrations for all carbon samples are shown in Table 4. 32,33…”
Section: Resultsmentioning
confidence: 99%
“…31 The ether/hydroxyl and carboxyl surface groups are thought to be beneficial in the hindering of the polysulfide-shuttle by immobilisation of the polysulfides; oxygen surface concentrations for all carbon samples are shown in Table 4. 32,33 The IR of the samples (see Fig. S5, ESI †) becomes far less complex with increasing pyrolysis temperature, due to the thermal etching of the resins' functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the preparation of heteroatom-doped core-shell porous carbon anode underwent a series of complex synthesis processes. Therefore, it is necessary to design a novel three-dimensional carbon structure with heteroatom doping and large porosity through a simple synthesis process to further promote the application of DC-PIHC [ 25 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The strong chemical affinity and promoted redox reaction kinetics can effectively alleviate the LiPSs shuttling, while the lithiophilic sites can induce uniform Li nucleation. [19][20][21][22] Besides the structural design and composition optimization, modulating the interface also can enhance the electrochemical properties of Li-S batteries. It has been well demonstrated that constructing heterostructural interface by coupling the strong adsorption capability and high electrocatalytic activity can significantly promote the adsorption-conversion kinetics of LiPSs on S cathode.…”
Section: Introductionmentioning
confidence: 99%